Pregnant women’s experiences and views on an “opt-out” referral pathway to specialist smoking cessation support: a qualitative evaluation - Sloan, Melanie; Campbell, Katarzyna; Bowker, Katharine; Coleman, Tim; Cooper, Sue; Brafman-Price, Barbara; Naughton, Felix (Oxford University Press, 2016)
Introduction: Smoking in pregnancy remains an important and costly public health concern with policy makers worldwide researching methods to aid cessation. UK government guidelines recommend implementation of an “opt-out” (ie, whether requested or not) referral pathway for pregnant smokers to specialist smoking cessation support using carbon monoxide (CO) screening. This study explores the views of pregnant smokers who experienced this new pathway in one UK hospital trust.